Interrupting prolonged sitting with frequent short bouts of light‐intensity activity in people with type 1 diabetes improves glycaemic control without increasing hypoglycaemia: The SIT‐LESS randomised controlled trial - Rachel Churm (Diabetes, Obesity and Metabolism, 2023)
Aim: To examine the impact of interrupting prolonged sitting with frequent short bouts of light-intensity activity on glycaemic control in people with type 1 diabetes (T1D). Materials and Methods: In total, 32 inactive adults with T1D [aged 27.9 ± 4.7 years, 15 men, diabetes duration 16.0 ± 6.9 years and glycated haemoglobin 8.4 ± 1.4% (68 ± 2.3 mmol/mol)] underwent two 7-h experimental conditions in a randomised crossover fashion with >7-day washout consisting of: uninterrupted sitting (SIT), or, interrupted sitting with 3-min bouts of self-paced walking at 30-min intervals (SIT-LESS). Standardised mixed-macronutrient meals were administered 3.5 h apart during each condition. Blinded continuous glucose monitoring captured interstitial glucose responses during the 7-h experimental period and for a further 48-h under free-living conditions. Results: SIT-LESS reduced total mean glucose (SIT 8.2 ± 2.6 vs. SIT-LESS 6.9 ± 1.7 mmol/L, p = .001) and increased time in range (3.9-10.0 mmol/L) by 13.7% (SIT 71.5 ± 9.5 vs. SIT-LESS 85.1 ± 7.1%, p = .002). Hyperglycaemia (>10.0 mmol/L) was reduced by 15.0% under SIT-LESS (SIT 24.2 ± 10.8 vs. SIT-LESS 9.2 ± 6.4%, p = .002), whereas hypoglycaemia exposure (<3.9 mmol/L) (SIT 4.6 ± 3.0 vs. SIT-LESS 6.0 ± 6.0%, p = .583) was comparable across conditions. SIT-LESS reduced glycaemic variability (coefficient of variation %) by 7.8% across the observation window (p = .021). These findings were consistent when assessing discrete time periods, with SIT-LESS improving experimental and free-living postprandial, whole-day and night-time glycaemic outcomes (p < .05). Conclusions: Interrupting prolonged sitting with frequent short bouts of light-intensity activity improves acute postprandial and 48-h glycaemia in adults with T1D. This pragmatic strategy is an efficacious approach to reducing sedentariness and increasing physical activity levels without increasing risk of hypoglycaemia in T1D.